Safe long-term therapy of Cushing’s syndrome over 37 years with mitotane - Seibold, Jonas; Hönemann, Mario; Tönjes, Anke; Sandner, Benjamin (Frontiers in Endocrinology, 2024)
While indicated, surgery is not always possible as first line treatment of Cushing's Disease (CD). In such cases, patients require medical therapy in order to prevent complications resulting from hypercortisolism. Although there has been a wide expansion in pharmacological options in recent years, mitotane was the agent of choice for treating hypercortisolism decades ago. Due to the introduction of other therapies, long-term experience with mitotane remains limited.Here, we report the case of a woman with CD who was treated with mitotane for 37 years.During the treatment period, biochemical and clinical disease control was achieved and the patient had two uncomplicated pregnancies. Drug related side effects remained moderate and could be controlled by several dose adjustments. Our case highlights the ability of mitotane to allow an effective control of hypercortisolism and to represent a safe treatment option in the special situation where CD requires an alternative therapeutic approach.Furthermore, we provide a literature review of long-term use of mitotane and reported cases of pregnancy in the context of mitotane therapy.